Isolation, identification and characterization of 2,2-dichloropropionic acid utilizing bacteria - Wong, Wen Yong (2013)
2,2-dichloropropionic acid (2,2-DCP) is an artificial halogenated compound used as herbicide. A bacterium able to utilize 2,2-DCP as sole carbon source was isolated from soil in Melaka rubber estate. The bacterium was identified as Labrys sp. strain Wy1 using bacterium’s 16S rRNA partial sequence. The cells doubling time was 34.6 hours in liquid minimal media supplied with 20 mM 2,2-DCP as sole carbon source. Utilization of 2,2-DCP was confirmed by detection of chloride ion released at 0.27 mM. An endophytic bacterium isolated from Axonopus compressus which was identified as Burkholderia cepacia strain Wy5 was also able to utilize 2,2-DCP as sole carbon source. The bacterium has cells doubling time 2.7 hours and chloride ion released was also detected at 47.28 ± 0.25 mM in minimal media contained 20 mM 2,2-DCP. Cell free extract (CFE) of Burkholderia cepacia Wy5 was further characterized due to its higher activity towards 2,2-DCP compared to Labrys sp. Wy1. Dehalogenase found in CFE of Burkholderia cepacia Wy5 has optimal enzyme specific activity at pH8 (0.83 µmol [Cl-] min-1 mg-1) and 40oC (0.78 µmol [Cl-] min-1 mg-1). The dehalogenase was also able to react with other a-haloalkanoic acid including monochloroacetic acid, DL-2-chloropropionic acid and DL-2-bromopropionic acid, but not 3-chloropropionic acid. “Group I” and “Group II” dehalogenase primers were used to amplify dehalogenase gene from both strains Wy1 and Wy5 but only Burkholderia cepacia Wy5 showed positive result. The dehalogenase gene fragment amplified was designated “deh-wy5” and subsequent analysis showed it belongs to Group I dehalogenase. Customized primers based on D,L-dex gene were designed to amplify complete sequence of deh-wy5 due to high similarity between partial sequence of deh-wy5 and D,L-dex. Complete sequence of deh-wy5 was eventually amplified and found to be identical (100%) to D,L-dex.